Graphing the Green route: Enzymatic hydrolysis in sustainable decomposition - Rajat Singh; Rajul Jain; Priyanka Soni; Sergio de los Santos-Villalobos; Sourav Chattaraj; Deblina Roy; Debasis Mitra; Ashish Gaur (Current Research in Microbial Sciences)
This graphical review article explores how sustainable decomposition contributes to environmental sustainability in waste management with a focus on enzymatic hydrolysis. Methods such as composting and anaerobic digestion efficiently break down organic waste and reduce landfill use and greenhouse gas emissions, while producing valuable resources such as compost and biogas. In particular, enzymatic hydrolysis offers advantages over chemical methods because it operates under mild conditions, targets specific substrates precisely, and yields purer products with fewer side reactions. Its renewable and biodegradable nature aligns with sustainability goals, making it suitable for waste decomposition, biorefining, and resource recovery. Enzymatic waste conversion reduces waste and pollution, conserves natural resources, and supports circular economy. Various ongoing studies have aimed to enhance the efficiency and environmental benefits of enzymatic hydrolysis, enabling innovative waste-to-value solutions that address environmental, economic, and social challenges. This article emphasizes the importance of its timely examination of enzymatic hydrolysis as a prominent method for sustainable waste decomposition, stressing its environmental, economic, and societal benefits. It distinguishes itself through its extensive analysis of chemical methods, its emphasis on the circular economy, and its delineation of future research directions and the need for interdisciplinary collaboration to advance this innovative technology.